KONSEP PERSAINGAN BISNIS DALAM ISLAM - Ridha, Sovia (Alhurriyah, 2015)
The business world is growing today have very possible occurrence of actions that benefit people and improve walfareness. But on the other hand there are many who are disadvantaged and oppressed kalnganmasyarakat due to the actions of business actors are just selfish and not thinking about the losses will befall others. therefore we need a rules that govern and become filters for businesses to do business. Tight business competition sometimes make businesses must squeeze the brain to implement competitive strategies that telling for his efforts to survive and at the same time increased. Therefore, Islam as a religion that rahmatan lil 'alamin provide constraints could be a reference for businesses in business and expand its business to a more advanced level. The basic principles of doing business competition has been described in the Qur'an and hadith the Prophet bik explicitly or through gestures.